![(x+y)^2\,\mathrm dx+(2xy+x^2-2)\,\mathrm dy=0](https://img.qammunity.org/2021/formulas/mathematics/college/w30co2mgi3d24ut4p3ujult5p495fle9q3.png)
Suppose the ODE has a solution of the form
, with total differential
![(\partial F)/(\partial x)\,\mathrm dx+(\partial F)/(\partial y)\,\mathrm dy=0](https://img.qammunity.org/2021/formulas/mathematics/college/jwfrbrd6tni9fyv6tjyq81ep1zp8uy842y.png)
This ODE is exact if the mixed partial derivatives are equal, i.e.
![(\partial^2F)/(\partial y\partial x)=(\partial^2F)/(\partial x\partial y)](https://img.qammunity.org/2021/formulas/mathematics/college/7zblyw61r5yo3b900abz2y94mxuatrfnok.png)
We have
![(\partial F)/(\partial x)=(x+y)^2\implies(\partial^2F)/(\partial y\partial x)=2(x+y)](https://img.qammunity.org/2021/formulas/mathematics/college/2x9fxask3emz3nnb4mdv5nag46l2lavl7z.png)
![(\partial F)/(\partial y)=2xy+x^2-2\implies(\partial^2F)/(\partial x\partial y)=2y+2x=2(x+y)](https://img.qammunity.org/2021/formulas/mathematics/college/sna0ocogoyoacikr2h1gtvh9jku7kziqt7.png)
so the ODE is indeed exact.
Integrating both sides of
![(\partial F)/(\partial x)=(x+y)^2](https://img.qammunity.org/2021/formulas/mathematics/college/a4xfbgh4rn0ftx5c6nhnnhjytjdf2tx3xg.png)
with respect to
gives
![F(x,y)=\frac{(x+y)^3}3+g(y)](https://img.qammunity.org/2021/formulas/mathematics/college/yi6p0daqz7t1t0unz6pepeeg56ldbrxyap.png)
Differentiating both sides with respect to
gives
![(\partial F)/(\partial y)=2xy+x^2-2=(x+y)^2+(\mathrm dg)/(\mathrm dy)](https://img.qammunity.org/2021/formulas/mathematics/college/72j0htv4147kri39euq2v0a3yjszfbf6b5.png)
![\implies x^2+2xy-2=x^2+2xy+y^2+(\mathrm dg)/(\mathrm dy)](https://img.qammunity.org/2021/formulas/mathematics/college/d2p7d5nzl0deenvjchihmv8hy5c4nxg249.png)
![\implies(\mathrm dg)/(\mathrm dy)=-y^2-2](https://img.qammunity.org/2021/formulas/mathematics/college/hm11vxmuv9ujc5jn1qrwjfw1zff66y18zp.png)
![\implies g(y)=-\frac{y^3}3-2y+C](https://img.qammunity.org/2021/formulas/mathematics/college/hd5af4dbj59k94blzb5a8a1j3b7274el5f.png)
![\implies F(x,y)=\frac{(x+y)^3}3-\frac{y^3}3-2y+C](https://img.qammunity.org/2021/formulas/mathematics/college/tvg4k7joap55ic1u2bozqsyzucgy75oy0x.png)
so the general solution to the ODE is
![F(x,y)=\frac{(x+y)^3}3-\frac{y^3}3-2y=C](https://img.qammunity.org/2021/formulas/mathematics/college/f8tmwjpcpxsy7u09ed4setqxemuwgaj7a7.png)
Given that
, we find
![\frac{(1+1)^3}3-\frac{1^3}3-2=C\implies C=\frac13](https://img.qammunity.org/2021/formulas/mathematics/college/c6f8ho0amd24a6oej1rvjrr4esyhw0hnny.png)
so that the solution to the IVP is
![F(x,y)=\frac{(x+y)^3}3-\frac{y^3}3-2y=\frac13](https://img.qammunity.org/2021/formulas/mathematics/college/2tf3mg3eyryt191243q2r7qkt8ygnrwcpr.png)
![\implies\boxed{(x+y)^3-y^3-6y=1}](https://img.qammunity.org/2021/formulas/mathematics/college/j8cgyy1uwp79mn5amq9wnd7jfpc8a3jl5c.png)